PENGENDALIAN GAS BUANG KENDARAAN BERMOTOR DI KOTA DENPASAR DENGAN PENDEKATAN KONSEP ATUR DIRI SENDIRI (ADS) - Putri Kusuma Kencanawati, Cok Istri (Bumi Lestari; Vol 4 No 1)
Industrialization Development which only pursue economic growth can causeenvironmental contamination, because development activity represent process intervence toenvironment. One of environmental control of contamination effort with the Concept ArrangeOwnself approach, the society can chosen most economic action, at one blow thegovernmental and environmental friendliness only ascertaining the activity walk inagreement corridor which must be obeyedResearch method of taken is research survai with quisioner propagating and,diskriptif. Quisioner intended for forecast attitude socialize to control from contamination ofair individually. The Subjek selected by incidental and who representing all motor vehicleconsumer, with education from high school and up and live in Town Denpasar.From the opinion done, have the special things, that awareness of society to pollutionof air is high enough. Others, renewable fuel use can be emboldened on condition that cheapand easy, while in overcoming danger of environmental contamination, socialize are tend totry beforehand to recovery, before reporting to governmental. This matter indicate thatsociety can arrange their self in lessening and also overcoming danger of environmentalcontamination.
Keywords: control, emission, approach